MODIFICATION OF DYNAMIC CONSTITUTIVE RELATION OF440C STAINLESS STEEL BASED ON J-C MODEL (MT) - WANG Liang; JIA HaiShen; ZHANG JiLin; LUO WenCui (Jixie qiangdu)
In order to construct a constitutive model that reasonably describes the changing relationship of flow stress of 440C stainless steel, quasi-static and dynamic compression experiments were carried out with the help of a universal testing machine and a Hopkinson compression bar device. Based on the obtained experimental data, the parameters of the original J-C constitutive model were calibrated, and its applicability and prediction accuracy for describing the stress-flow behavior of the studied materials were discussed. Based on the analysis results, a modified J-C constitutive model considering the coupling among strain, strain rate and temperature was proposed, and the model parameters were calibrated. The experimental data and the model predicted value were compared and analyzed, and the validity of the proposed model was evaluated by three statistical parameters: correlation coefficient R, average relative error AARE and root mean square deviation RMSE. The results show that the dynamic mechanical behavior of 440C stainless steel is jointly dominated by the coupling between strain, strain rate and temperature. The correlation coefficient R of the proposed modified J-C constitutive model is 0.995 9, the average relative error AARE is 0.073, and the root mean square deviation RMSE is 0.761 8, which can reasonably describe its stress flow behavior.